Interfacing SAW resonators for wireless high temperature applications - Sarraf, Mohammad Javadian; Hamidon, Mohd Nizar; Mohd Isa, Maryam; Ismail, Alyani; Zarabi, Amir Reza (International Frequency Sensor Association Publishing, 2011)
In the recent year, wireless sensor has become the interest of research due to their ability to monitor remotely especially in harsh condition. Here a double surface acoustic wave (SAW) resonator system for wireless high temperature sensor application is discussed. The system also did not need any external power source to function, which made them as a passive system. In this paper, the principle of the system is discussed in detail together with simulation results. Finally, the suitable materials used to develop the system which includes the interconnection at the high temperatures are also been discussed.